Celebrity of Instagram and Endorsements: Shaping and Constructing Social Identity - Rahma Santhi Zinaida; Eku Diantara; Zaid Amin (Jurnal the Messenger, 2025)
Purpose: This research aims to explore how endorsements by celebrities on Instagram play a role in the formation and development of social identities among users. It will investigate the psychological processes, including relationships and the desire for social connection, that influence the link between celebrity impact and identity development.